Análisis y simulación de un rectificador trifásico controlado Active Front End (AFE) (2015)
This paper presents a result of research financed with own resources; It presents a state-space model of a three-phase controlled Active Front End rectifier. Using this model, we design a control law oriented voltage (VOC), directed to behavior as resistive load, unity power factor, which is tested by simulation using SimPowerSystem Toolbox in Matlab - Simulink ®.